2015
DOI: 10.3892/mmr.2015.4005
|View full text |Cite
|
Sign up to set email alerts
|

YAP is closely correlated with castration-resistant prostate cancer, and downregulation of YAP reduces proliferation and induces apoptosis of PC-3 cells

Abstract: Yes-associated protein 65 (YAP65) has been implicated as an oncogene, and its expression is increased in human cancer. Previous studies have demonstrated that alterations in YAP activity may result in tumourigenesis of the prostate. With androgen deprivation therapies becoming progressively ineffective, often leading to life-threatening androgen-resistant prostate cancer (CRPC). The present study aimed to analyse the role of YAP in prostate cancer (PCa), particularly in CRPC. YAP protein was detected using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The YAP1 and AMPK signaling pathways play momentous parts in tumour [25,26]. Previous studies had reported that YAP1 and AMPK pathways are activated in PC and the two pathways are involved in the pathogenesis of PC [27,28]. Research demonstrated circ0023404 exerted its efficacy via YAP1 signaling pathways [29] and other research demonstrated that circ0008274 exerted its efficacy by AMPK signaling pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…The YAP1 and AMPK signaling pathways play momentous parts in tumour [25,26]. Previous studies had reported that YAP1 and AMPK pathways are activated in PC and the two pathways are involved in the pathogenesis of PC [27,28]. Research demonstrated circ0023404 exerted its efficacy via YAP1 signaling pathways [29] and other research demonstrated that circ0008274 exerted its efficacy by AMPK signaling pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR. The isolation of total RNA and RT-qPCR were performed as described previously (19). All samples were amplified in triplicate.…”
Section: Patients and Tissuesmentioning
confidence: 99%
“…Increasing evidence has suggested the important roles of YAP in regulating PCa cell behavior (18,19). To the best our knowledge, no previous study has focused on the role of YAP within human PCa DU145 cells.…”
Section: Introductionmentioning
confidence: 97%